Investigating antimicrobial properties of lactobacillus culture towards food spoilage microorganisms - Ganesan, Vinita (2018)
In the 21st century, where several technological breakthroughs and cures are being discovered by scientists, food spoilage is still a recurring problem. Several antibiotic drugs discovered to combat food spoilage are no longer able to defeat the spoilage microorganisms due to antibiotic resistance. Antibiotic resistance occurs due to over usage of antibiotics. Moreover, consumers are also wanting foods to possess much fewer additives and be less heavily preserved. Food spoilage has resulted in much heavy economic losses. Thus, there is a need to find an alternative source of antimicrobial product to combat food spoilage microorganisms. The main goal of this project is to endeavour the antimicrobial efficacy towards food spoilage organisms through the introduction of Lactobacillus culture. PCR and PCR purification tests were carried out to identify the Lactobacillus species tested, which is Lactobacillus casei. Agar diffusion test was also carried out and it has proved that Lactobacillus casei does display antimicrobial properties and inhibit the growth of microorganisms.